Promoting Rice Field Fisheries in the Cambodian Mekong Delta - Sean, Vichet; Sithirith, Mak; Bernardo, Eisen (WorldFish, 2024)
In partnership with the Fisheries Administration (FiA) and GIZ, WorldFish recently conducted an exposure visit focusing on best practices for the management of rice field fisheries (RFF) in Kampong Thom province. The visit was attended by representatives from the Community Fish Refuges (CFRs) committee in the Mekong Delta and the upper Mekong provinces.